Love, Lies, and Control: A Cyberpsychological Analysis of Technology-Facilitated Abuse in Intimate Relationships - Gibbs, Tiphanie (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Technology-facilitated abuse is a growing form of intimate partner violence where digital tools are used to control, monitor, and intimidate victims. This study aimed to examine how certain technologies—such as social media, GPS tracking, and messaging apps—are enabling perpetrators to exert coercive control over their victims. Findings showed that when abusers use these technologies, the nature of the resulting psychological and emotional harm is uniquely severe and impactful. Some of the study's victim participants described heightened levels of anxiety, depression, and PTSD as a direct result of their abusive partner using technology against them. The research also identified several troubling legal and ethical gaps in our current societal framework that leave victims vulnerable. Focusing on a blended demographic sample of study participants—across gender and age—it became clear that certain groups are being targeted more than others. The study concludes by applying a cyberpsychological framework to the issue under investigation and making urgent safety recommendations.